2018
DOI: 10.15252/embj.201798786
|View full text |Cite
|
Sign up to set email alerts
|

A mitochondrial FUNDC1/HSC70 interaction organizes the proteostatic stress response at the risk of cell morbidity

Abstract: Both protein quality and mitochondrial quality are vital for the cellular activity, and impaired proteostasis and mitochondrial dysfunction are common etiologies of aging and age‐related disorders. Here, we report that the mitochondrial outer membrane protein FUNDC1 interacts with the chaperone HSC70 to promote the mitochondrial translocation of unfolded cytosolic proteins for degradation by LONP1 or for formation of non‐aggresomal mitochondrion‐associated protein aggregates (MAPAs) upon proteasome inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(80 citation statements)
references
References 54 publications
1
78
0
1
Order By: Relevance
“…has been shown to be involved in delivery of cytosolic proteins to the nucleus, mitochondrion and endoplasmic reticulum. 24,25 Due to this interaction and the observation that Hsc70 recognizes mitochondrial aspartate aminotransferase but not cytosolic, 26,27 we reason that our protocol is consistent with the expectation of producing biologically relevant interactions. [28][29][30][31] Based on these data we proceeded to analyze all 115 visible bands between 10 and 250 kDa in Figure 1A.…”
Section: Resultssupporting
confidence: 62%
“…has been shown to be involved in delivery of cytosolic proteins to the nucleus, mitochondrion and endoplasmic reticulum. 24,25 Due to this interaction and the observation that Hsc70 recognizes mitochondrial aspartate aminotransferase but not cytosolic, 26,27 we reason that our protocol is consistent with the expectation of producing biologically relevant interactions. [28][29][30][31] Based on these data we proceeded to analyze all 115 visible bands between 10 and 250 kDa in Figure 1A.…”
Section: Resultssupporting
confidence: 62%
“…The stressors leading to senescence include telomere shortening due to replicative exhaustion, DNA or chromatin structure and mitochondrial dysfunction [15][16][17][18][19]. Recent reports indicated that mitochondrial dysfunction plays an important role in initiating inflammatory responses and cellular senescence and has significance in the pathogenesis of lung disease [20]. ROS generation occurs via tissue damageactivated RAC1 and dysfunctional mitochondrial.…”
Section: Discussionmentioning
confidence: 99%
“…The second group of mitophagy receptors [20] contains a transmembrane domain that can directly bind to the OMM and stimulate autophagosome formation via their LIR motifs, namely Bnip3 (BCL2 interacting protein 3) [71], Nix/Bnip3L (BCL2-like 3) [72], FUNDC1 (FUN14 domain containing 1) [73] and Bcl2L13 (BCL2-like 13) [74]. Their roles in the regulation of cell proliferation, cytosolic protein degradation and cell death have also been reported [75][76][77]. However, their importance in mitochondrial clearance is not clearly known.…”
Section: Conflicts Of Interestmentioning
confidence: 99%